Variation in the formant of ethno-regional varieties in Nigerian English vowels - Amoniyan Oluwasegun (Open Linguistics)
Unlike previous studies on Nigerian English (NigE) that consistently report mid-point analysis to describe NigE vowels, this study employs spectral changes because it reveals inherent changes, which characterize vowel formants over time. Earlier research, for example, claims that a sub-variety of NigE (e.g., Western Nigerian English – WNigE) does not have phonetic differences between tense and lax. This study, therefore, examines the nature of the dynamic spectral changes of WNigE high and low lexical sets (such as TRAP/BATH, KIT/FLEECE, and FOOT/GOOSE) produced by 75 WNigE speakers who are born and raised, and currently reside in the west, east, and north of Nigeria. Two- and nine-point vowel measurements were employed to estimate the formant dynamics with F1 and F2 vector length, trajectory length (TL), formant velocity, and formant trajectories with the Generalized Additive Mixed Model. The results show the importance of examining the WNigE vowel using nine-point measurements rather than the two-point or mid-point. Our results reveal that WNigE vowels have phonetic differences, evidenced in formant trajectories. Social and linguistic factors also affect WNigE vowel production. Regions influence the TL of vowels, with WNigE speakers in the north and west regions showing longer TL than those in the east.